An Islamic theoretical framework for economic analysis - Laluddin, Hayatullah; Abdul Razak, Mohd Abbas (Scholars Academic and Scientific Publisher, 2021)
Conventional economics despite its scientific approach and positive arguments failed to solved the current economic problems of the humanity. There are two reasons for such failure; one reason is the positivity of its nature which hinders it from playing active role in controlling human behavior. And the second reason is that its basic postulates by themselves are the causes of the creation of the economic problems. This state of the affairs, necessitate, a complete departure from the contemporary conventional wisdom, in search of solution, to an alternative framework. An Islamic framework of economic analysis could present a viable alternative in the context, due to its dynamic nature, combining both material and spiritual aspects of human economic behaviors. Therefore, this article attempts to provide some insights into the early efforts by Muslim scholars in development the science of Islamic economics. It also underscores the inadequacy of the conventional economics theory and its causes, and the need for formulation of Islamic theory of economics. Philosophical framework of Islamic economics along with some major axioms of Islamic ethics, shaping Islamic outlook on economics are also dealt with. The distinctive features of an Islamic framework for economic analysis are also delineated in this article. Using an analytical approach, the article concludes the urgency of the need for the articulation of a comprehensive Islamic framework for Islamization of economic, hence, solving the contemporary economic problems of the humanity.